Expected yield and economic improvements of a yam seed system in West Africa using agro‐physiological modelling - Denis Cornet; Jorge Sierra; Régis Tournebize; Komivi Dossa; Benoît Gabrielle (Plants, People, Planet)
Societal Impact Statement Yam is a major tropical root crop and a staple food for millions of people in West Africa. The model used in this study shows that promoting the use of improved seed tubers would help increase yields and profitability for farmers. This could lead to improved food security, increased income and higher standards of living. Additionally, the model serves as a useful decision‐support tool for farmers and technicians to choose, depending on the species, the optimum seed‐tuber weight and planting date. This study provides agronomic arguments to justify investments in the improvement of yam planting materials in West Africa. Summary Yam (Dioscorea spp.) is a major tropical root crop, grown mainly in West Africa using traditional extensive techniques. Farmers typically reuse seed tubers by setting aside up to 30% of their production for the next season, leading to high planting material variability that affects yields. Several initiatives aim to promote the use of improved seed tubers. However, to help their adoption, it is necessary to quantify the agronomic and economic advantages. To address this, a model for individual plant growth and development was developed based on six experiments in Benin from 2007 to 2009. This model simulates the combined effect of emergence (through photoperiod and temperature) and seed‐tuber weight on yam plant growth and development. Its predictions were highly correlated with observed plant tuber yield (R2 > 0.83). Results highlight the crucial role of key processes such as seed‐tuber physiological age and photoperiod sensitivity. The study shows that for the traditional planting dates, the use of improved planting material could lead to a yield increase of 22%–27% and a gain in profitability of 30% and 40% for Dioscorea alata and Dioscorea rotundata, respectively. The model proved to be a useful decision‐support tool for choosing an optimum seed‐tuber weight, depending on the species and the planting date. This study validates investments in yam seed systems in West Africa. However, beyond seed size and health, other factors such as dormancy, storage time and their management need to be considered to address emergence heterogeneity and its impact on yield.